1993
DOI: 10.1007/bf01845901
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive style perspective on ethical questions

Abstract: Previous research has shown that cognitive style impact s several areas of human behavior of interest to marketers. This article reports the results of an exploratol T study testing the proposition that cognitive style can influence one's perceptions of what is and is not a matter of ethics. The findi,lgs indicate that cognitive style can play a role in one's perceptions of ethics, and may help further our understanding of the factors that bear on ethical points of view.Questions about what is and what is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…There is a growing literature in the area of cognitive styles with respect to ethical decisionmaking. McIntyre and Capen (1993), for example, conducted an empirical study using Fleming's (1985) typology of cognitive styles (based upon a classification using the Myers-Briggs typology) and reported that cognitive style can influence whether or not one considers an issue to be ethical in nature, that is the initial framing of issues as ethical. Snow and Bloom (1992) also conducted some empirical work on ethical decision-making styles using an initial theoretically-derived group of seven distinct styles (grouped into either ends-oriented or meansoriented styles).…”
Section: The Psychology Of Ethics: Moral Developmentmentioning
confidence: 99%
“…There is a growing literature in the area of cognitive styles with respect to ethical decisionmaking. McIntyre and Capen (1993), for example, conducted an empirical study using Fleming's (1985) typology of cognitive styles (based upon a classification using the Myers-Briggs typology) and reported that cognitive style can influence whether or not one considers an issue to be ethical in nature, that is the initial framing of issues as ethical. Snow and Bloom (1992) also conducted some empirical work on ethical decision-making styles using an initial theoretically-derived group of seven distinct styles (grouped into either ends-oriented or meansoriented styles).…”
Section: The Psychology Of Ethics: Moral Developmentmentioning
confidence: 99%
“…However, surprisingly few studies (e.g., Fleming, 1985;McIntyre and Capen, 1993;McIntyre, Capen, and Minton, 1995;Pennino, 2002) have investigated the empirical link between managerial thinking styles and the commonly accepted components of ethical decisionmaking: ethical awareness, judgment, intent, and action (Jones, 1991;Rest, 1986;Street et al, 1997). Indeed, OÕFallon and ButterfieldÕs (2005) recent review of the empirical ethical decision-making literature concluded that an important future research direction is investigating the manner in which individuals seek relevant information concerning an ethical dilemma, cognitively interpret such information, and then form behavioral intent and action.…”
Section: Introductionmentioning
confidence: 98%
“…At least partially socialized, thinking styles may vary depending on the conditions and demands of a given situation (Sternberg, 1997(Sternberg, , 1994(Sternberg, , 1988. Scholars have adopted a range of theoretical models and measures for assessing thinking style in studies of ethical decision-making, including the Myers-Briggs Type Indicator (MBTI) (e.g., Fleming, 1985;McIntyre and Capen, 1993;McIntyre, Capen, and Minton, 1995;White and Manolis, 1997), the Decision-Style Inventory (DSI) (e.g., Pennino, 2002), and the Learning Style Inventory (LSI) (White and Manolis, 1997). The popular and somewhat controversial MBTI assesses four attitudes or orientations (extroversion vs. introversion, judging vs. perceiving) and four functions (sensing vs. intuition, thinking vs. feeling).…”
mentioning
confidence: 99%
“…Another important, but underdeveloped, aspect of international business ethics concerns the relationship between the thinking style of managers and their managerial ethical decisionmaking. Literature has revealed that managers with different thinking styles, or cognitive style, perceive ethical situations or dilemmas very differently (Fleming, 1985;McIntyre and Capen, 1993;Pennino, 2002). For instance, what seems to be a matter of ethics for some people with a certain thinking style may have no ethical implications for other people with a different thinking style (McIntyre and Capen, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Literature has revealed that managers with different thinking styles, or cognitive style, perceive ethical situations or dilemmas very differently (Fleming, 1985;McIntyre and Capen, 1993;Pennino, 2002). For instance, what seems to be a matter of ethics for some people with a certain thinking style may have no ethical implications for other people with a different thinking style (McIntyre and Capen, 1993). Much of the empirical literature has demonstrated the varying influence of linear (i.e., sensing/thinking) and nonlinear (i.e., intuition/feeling) elements in thinking style on the ethical decision-making, typically utilizing the Myers-Briggs Type Indicator (MBTI) (e.g., McIntyre and Capen, 1993;McIntyre, Capen, and Minton, 1995;White and Manolis, 1997).…”
Section: Introductionmentioning
confidence: 99%